Attachment insecurities, caregiver burden, and psychological distress among partners of patients with heart disease - Laflamme, Simone Zofia; Bouchard, Karen; Sztajerowska, Karolina; Lalande, Kathleen; Greenman, Paul S.; Tulloch, Heather (PloS one, 2022)
Caregiver psychological distress (i.e., depression and anxiety) is harmful to both caregiver and patient. Different affect-regulation strategies associated with attachment orientations may impact a caregiver’s perception of their caregiving role as a burden, thereby contributing to their psychological distress. The aim of the present investigation was to examine the links among attachment orientations, caregiver burden, and psychological distress in a cardiac context. Participants ( N = 181, M age = 61.79, SD = 10.49; males = 24.7%) were romantic partners of patients with heart disease (i.e., informal caregivers) who completed validated questionnaires. The majority of caregivers had partners with coronary artery disease ( n = 127, 70. 2%). 66.3% of caregivers reported low burden, 87.6% reported low levels of depression and 89.9% reported low levels of anxiety. The mean anxious attachment score was 2.74 ( SD = 1.37) and the mean avoidant attachment score was 2.95 ( SD = 1.26). Four mediation analyses were run using PROCESS macro for IBM SPSS (version 26). Statistical models showed that the relationships between attachment anxiety and psychological distress were mediated by caregiver burden [ ab anxiety = 0.15, 95% C . I . (0.04, 0.29); ab depression = 0.15, 95% C . I . (0.05, 0.28)] and that attachment avoidance was not a significant covariate ( cv anxiety = −0.02, p >0.05; cv depression = 0.40, p >0.05). The relationships between attachment avoidance and psychological distress were also mediated by caregiver burden [a b anxiety = 0.23, 95% C . I . (0.10, 0.42); ab depression = 0.21, 95% C . I . (0.09, 0.37]with attachment anxiety as a significant covariate ( cv anxiety = 1.09, p <0.001; cv depression = 1.09, p <0.001). Interventions for caregivers reporting attachment insecurity and burden should be explored to potentially lessen caregiver distress as they support their partners with heart disease.